2010
DOI: 10.1007/978-1-4419-6211-9_13
|View full text |Cite
|
Sign up to set email alerts
|

Quaternion Algebras with the Same Subfields

Abstract: Abstract. G. Prasad and A. Rapinchuk asked if two quaternion division F -algebras that have the same subfields are necessarily isomorphic. The answer is known to be "no" for some very large fields. We prove that the answer is "yes" if F is an extension of a global field K so that F/K is unirational and has zero unramified Brauer group. We also prove a similar result for Pfister forms and give an application to tractable fields.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
0
20
0
1
Order By: Relevance
“…Garibaldi and Saltman [GS10] showed that if F has trivial "unramified Brauer group" (in a sense including the archimedean places), then any two quaternion division algebras over F having the same maximal subfields must be isomorphic. Rapinchuk and Rapinchuk proved similar results for period 2 division algebras in [RR09].…”
Section: Amitsur Conjecturementioning
confidence: 99%
“…Garibaldi and Saltman [GS10] showed that if F has trivial "unramified Brauer group" (in a sense including the archimedean places), then any two quaternion division algebras over F having the same maximal subfields must be isomorphic. Rapinchuk and Rapinchuk proved similar results for period 2 division algebras in [RR09].…”
Section: Amitsur Conjecturementioning
confidence: 99%
“…Lemma 2.3 of [40] (see also [20], Lemma 3.1) now shows that for any set V of discrete valuations of K, we have gen(D) ⊂ gen V (D).…”
Section: Some Other Notions Of the Genusmentioning
confidence: 88%
“…Several people, including Garibaldi, Rost, Saltman, Schacher, Wadsworth, and others have given a construction of quaternion algebras with non-trivial genus over certain very large fields of characteristic ̸ = 2. 2 We refer the reader to [20], § 2 for the full details, and only sketch the main ideas here.…”
Section: Example 32 Letmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for even finitely generated fields, there are open questions. In [3], Garibaldi and Saltman produce an infinitely generated field over which there are two nonisomorphic weakly isomorphic quaternion division algebras. With this in mind define the genus of D to be the set:…”
Section: Introductionmentioning
confidence: 99%